The Development Of Physical Condition Training To Improve Players Performance In Traditional Sports Galah Hadang At Adolescent Age - Nevi Hardika; Rusdi Rusdi; M Sabransyah; Asmutiar Asmutiar; Zainal Arifin (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
This research aims to: 1) Develop a game-based basic motion learning skills model in upper-grade elementary school children. 2) Obtain empirical data about the effectiveness of the results of the development of learning models based on basic motion skills in primary school children. Method: using Research & Development from Borg & Gall with qualitative and quantitative approaches. The subjects of this study were 06 East Pontianak Elementary School and 34 South Pontianak Elementary School with 22 effectiveness test objects. Data collection techniques using descriptive qualitative (Expert Judgment). Analysis techniques data in this study used a qualitative percentage and a different test (t-test) at α = 0.05. From the results of small-scale trial data recapitulation (n = 10) with the mean results obtained of 283 with a percentage of 78% categorized as Good. With the result 2 students are in very good category, 6 students are in good category and 2 students are in enough category. While the results of large-scale trial data recapitulation (n = 20), the mean result obtained is 600 with a percentage of 83% in the Good category. With the results of 12 students in very good category, 8 students in good category. While the effectiveness test (t-test) can be proven by the pretest group and the posttest group showing the value of  tcount  (12,122) > ttable (2.0797) with a significance of 0.000 > 0.05. Meanwhile, the results of the posttest t-test results with the control group showed that the value of tcount (10.350) > ttable (2.0797) with a significance of 0.000 > 0.05. This shows that the data from the two groups have a significant variance, namely the value of tcount > ttable. This shows that there is a significant difference so that it can be generalized and from the results of the difference between the pretest and posttest group means is 9.28 with an increase of 5.17%. Meanwhile, the mean difference between the posttest group and the control group was 5.14 with an increase of 2.80%. Therefore, it can be concluded that the development of a physical condition training model can improve the performance of players in traditional sports galah hadang in adolescence effectively and efficiently so that it can be applied to athletes.